Patient understanding and acceptability of an early lung cancer diagnosis trial: a qualitative study - Prout, H; Barham, A; Bongard, E; Tudor-Edwards, R; Griffiths, G; Hamilton, W; Harrop, E; Hood, K; Hurt, C; Nelson, R; Porter, C; Roberts, K; et al. (BioMed Central, 2018)
Background The ELCID (Early Lung Cancer Investigation and Diagnosis) trial was a feasibility randomised controlled trial examining the effect on lung cancer diagnosis of lowering the threshold for referral for urgent chest x-ray for smokers and recent ex-smokers, aged over 60 years with new chest symptoms. The qualitative component aimed to explore the feasibility of individually randomising patients to an urgent chest x-ray or not and to investigate any barriers to patient recruitment and participation. We integrated this within the feasibility trial to inform the design of any future definitive trial, particularly in view of the lack of research exploring symptomatic patients’ experiences of participating in diagnostic trials for possible/suspected lung cancer. Although previous studies contributed valuable information concerning screening for lung cancer and patient participation in trials, this paper is the first to explore issues relating to this specific patient group. Methods Qualitative interviews were conducted with 21 patients, comprising 9 who had been randomised to receive an immediate chest x-ray, 10 who were randomised to receive the standard treatment according to the National Institute for Health and Care Excellence guidelines, and 2 who chose not to participate in the trial. Interviews were analysed using a framework approach. Results The findings of this analysis showed that altruism, personal benefit and the reassurance of not having lung cancer were important factors in patient participation. However, patients largely believed that being in the intervention arm was more beneficial, highlighting a lack of understanding of clinical equipoise. Disincentives to participation in the trial included the stigmatisation of patients who smoked (given the inclusion criteria). Although the majority of patients reported that they were happy with the trial design, there was evidence of poor understanding. Last, for several patients, placing trust in health professionals was preferred to understanding the trial processes. Conclusions The integration of a qualitative study focusing on participant experience as a secondary outcome of a feasibility trial enabled exploration of patient response to participation and recruitment. The study demonstrated that although it is feasible to recruit patients to the ELCID trial, more work needs to be done to ensure an understanding of study principles and also of smoking stigmatisation.